Correction to: Carbon Black as a Modifier for a Cheap Carbon Paper Disposable Electrode for the Determination of Zaleplon in Synthetic Saliva (Journal of Applied Electrochemistry, 2024 10.1007/S10800-024-02240-7) - Aguirre-Quintana, M; Aguirre-Quintana, M; Navarro-Gajardo, F; Navarro-Gajardo, F; Pizarro-Reyes, J; Pizarro-Reyes, J (Springer Science and Business Media B.V., 2025)
In the original published article, the affiliation details for author “Erick Flores” were incorrectly given as ‘Departamento de Química de los Materiales, Facultad de Química y Biología, Universidad de Santiago de Chile (USACH), Santiago, Chile’ but should have been ‘Instituto de Química y Bioquímica, Facultad de Ciencias, Universidad de Valparaíso, Avda. Gran Bretaña 1111, Playa Ancha, Valparaíso, Chile.’ The original article has been corrected. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.